(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The present study aimes to identify the relationship between locus of control and healthy behavior among a sample of adults in Latakia city. It also aimes to determine each of the locus of control and healthy behavior and to discover the differences between them on these variables according to gender . The study sample consisted of (100) adults (44 males and 56 females),whome were randomly selected among different adults in Latakia city. I (the researsher ) used a the scale of the locus of control (prepared by the Canadian society) and the scale of the healthy behavior (prepared by the researcher ). Results of the study confirmed that there were no statistically significant differences between locus of control and the healthy behavior on the studied sample . The results showed that respondents tend to the positive healthy behavior and there was an orientation towards internal controls.The study found that there were significant differences in healthy behavior according to the variable of sex ( the differences were in favor of females) , and there were no significant differences in the locus of control according to sex.